An Empirical Study on the Relationship of Shopping Motives on the Retail Store Dimensions with Special Reference to Women Shoppers in Puducherry - K Ramprabha (International Journal of Supply Chain Management, 2018)
Shopping motives can be described as consumers needs and wants as they are concerned to stores at which to make the purchase. Motivation in general is defined as an internal drive that reflects goal-oriented arousal (Arnould, Price, and Zinkhan, 2002). In a shopping context, motivation can be described as the vibrant force inside consumers that makes them shop. The Indian retail picture has undergone a momentous transformation in the consumer shopping behaviour. This situation makes it important to study the attributes that have an effect on the consumer shopping experience. Motivation is considered to be the major reason to shop in a particular way. They are the primary driving force within the consumers for which they shop. Motivation affects shopping behaviour and is responsible for various shopping activities in the stores. It influences the way the shoppers distinguish the environment of the retail store. This article provides an insight about the retail store attributes that has an influence over the shopping motivations and their effect on women shoppers. To identify the relationship of shopping motives on the dimensions of retailing, a scale was generated, validated and compared with the retail factors of the store. It is observed that shopping motivation is optimistically correlated with the retail factors of the store.